Bank Competition and Profitability in South East Asia (The Indonesian Journal of Business Administration, 2022)
Abstract. Using bank-level data for periods 2010-2019, this study investigates the effect of competition and bank profitability in six South East Asian countries (Indonesia, Malaysia, Philippines, Singapore, Thailand, and Vietnam). The investigation is conducted by applying Panzar and Rosse (1987) methodology to characterize the competitive environment in South East Asian banking sector and followed by examination of profitability and market structure relations to determine variables that affect bank profitability. The result indicate Singapore to be highly concentrated and at times have monopoly environment, while the other five observed countries are less concentrated and have monopolistic competition. Investigation of bank profitability relationship shows market power and market concentration have no positive significant impact on bank profitability. The effect of bank-level variables have more significance on bank profitability, although impacting variables differ for different South East Asian banking markets. Keywords: ASEAN banking, bank competition, bank profitability, market structure, Panzar and Rosse